Physical Disability and Sexuality Stories from South Africa - Hunt, Xanthe; Braathen, Stine Hellum; Chiwaula, Mussa; Carew, Mark T.; Rohleder, Poul.; Swartz, Leslie; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
This open access edited volume explores physical disability and sexuality in South Africa, drawing on past studies, new research conducted by the editors, and first-person narratives from people with physical disabilities in the country. Sexuality has long been a site of oppression and discrimination for people with disabilities based on myths and misconceptions, and this book explores how these play out for people with physical disabilities in the South African setting. One myth with which the book is centrally concerned, is that people with disabilities are unable to have sex, or are seen as lacking sexuality by society at large. Societal understandings of masculinity, femininity, bodies and attractiveness, often lead people with physical disabilities to be seen as being undesirable romantic or sexual partners. The contributions in this volume explore how these prevailing social conditions impact on the access to sexual and reproductive healthcare, involvement in romantic relationships, childbearing, and sexual citizenship as a whole, of people with physical disabilities in the Western Cape of the country. The authors' research, and first person contributions by people with physical disabilities themselves, suggest that education and public health policy must change, if the sexual and reproductive health rights and full inclusion of people with disabilities are to be achieved. Xanthe Hunt is Senior Researcher at Stellenbosch University, South Africa. Stine Hellum Braathen is Research Manager at SINTEF, Norway. Mussa Chiwaula is Director of the Southern African Federation of the Disabled, Botswana. Mark T. Carew is Honorary Research Associate at the UCL International Disability Research Centre, UK. Poul Rohleder is Senior Lecturer at the University of Essex, UK. Leslie Swartz is Distinguished Professor of Psychology atStellenbosch University, South Africa.
Chapter 1: Introduction (Xanthe Hunt, Leslie Swartz, Stine Hellum Braathen, Mark Carew, Mussa Chiwaula, and Poul Rohleder) -- Chapter 2: Disability and Sport (Rosabelle Riese, Xanthe Hunt, and Leslie Swartz) -- Chapter 3: Myths and Misconceptions about Sexuality and Disability (Stine Hellum Braathen, Mark Carew, Mussa Chiwaula, and Poul Rohleder) -- Chapter 4: Desexualizing of Disability (Martha Geiger, Xanthe Hunt, Mussa Chiwaula, and Leslie Swartz) -- Chapter 5: Disability and femininity (Stine Hellum Braathen, Xanthe Hunt, and Poul Rohleder) -- Chapter 6: Kate$1 (Bs story: femininity and sexuality (Kate, Xanthe Hunt, and Stine Hellum Braathen) -- Chapter 7: Disability and masculinity (Leslie Swartz, Jason Bantjes, and Poul Rohleder) -- Chapter 8: Bongani$1 (Bs story: young man's disability, his sexuality and relationships (Bongani Mapumulo, Leslie Swartz, and Jason Bantjes) -- Chapter 9: Sexual and reproductive health (Xanthe Hunt, Leslie Swartz, Stine Hellum Braathen, Mark Carew, Mussa Chiwaula, and Poul Rohleder) -- Chapter 10: Parenthood and Disability (Vic McKinney, Leslie Swartz, and Mark Carew).s
Keywords: Africa -- Politics and government; Economic development; Social medicine; African Politics; Development Studies; Health, Medicine and Society